UJI FORMULASI KUALITAS PUPUK KOMPOS YANG BERSUMBER DARI SAMPAH ORGANIK DENGAN PENAMBAHAN LIMBAH TERNAK AYAM, SAPI, BABI DAN TANAMAN PAHITAN - Supadma, A.A. Nyoman; Arthagama, Dewa Made (Bumi Lestari, 2012)
Research dealing with effects of organic rubbish and waste formulation on the quality of compost fertilizer was conducted in Agriculture Experiment Station, Faculty of Agriculture, Udayana University, Pegok, Denpasar, between June and October, 2007. The experiment utilized Randomized Complete Design, one factor with 10 formulation treatments and 3 replications. The treatments namely: A (100 % organic rubbish), B (75 % organic rubbish + 25 % pahitan plant), C (50 % organic rubbish + 50 % pahitan plant), D (75 % organic rubbish + 25 % waste of chicken cages), E (50 % organic rubbish + 50 % waste of chicken cages), F (75 % organic rubbish + 25 % waste of cow cattle), G ( 50 % organic rubbish + 50 % waste of cow cattle), H (75 % organic rubbish + 25 % waste of pig cattle), I (50 % organic rubbish + 50 % waste of pig cattle), and J (50 % organic rubbish + 12.5 % waste of cow cattle + 12.5 % waste of chicken cattle + 12.5 % waste of pig cattle + 12.5 % pahitan plant). The results showed that the treatment was highly significant to all parameters of compost at seven weeks incubation. The best formulation was E treatment, it was supported by increasing total nitrogen (1,61 %), available phosphorus (5,83 g/kg), Cation exchange capacity (CEC) (41,70 me/100 g), but decreasing C/N ratio (17,14), pH (7,07) and electric conductivity (very low).
Keywords: formulations, compost, organic rubbish, waste